Governance of Arctic Shipping Rethinking Risk, Human Impacts and Regulation - Chircop, Aldo; Goerlandt, Floris; Aporta, Claudio; Pelot, Ronald (Springer Polar Sciences, 2020)
This open access book is a result of the Dalhousie-led research project Safe Navigation and Environment Protection, supported by a grant from the Ocean Frontier Institute's the Canada First Research Excellent Fund (CFREF). The book focuses on Arctic shipping and investigates how ocean change and anthropogenic impacts affect our understanding of risk, policy, management and regulation for safe navigation, environment protection, conflict management between ocean uses, and protection of Indigenous peoples' interests. A rapidly changing Arctic as a result of climate change and ice loss is rendering the North more accessible, providing new opportunities while producing impacts on the Arctic. The book explores ideas for enhanced governance of Arctic shipping through risk-based planning, marine spatial planning and scaling up shipping standards for safety, environment protection and public health.